A escrita do tempo e a escrita da memória: processo histórico e masculinidade em José Lins do Rego (1924-1934) - Dias, Ana Lívia Alves (2023)
Starting from contacts between two diverse discursive spaces, history and literature, this thesis aimed to understand the practices of being a man, which were experienced inside of a mill society, as they were created by the writer José Lins do Rego. By the end of the 19th century and in the first decades of the 20th century, Brazil's modernization process was noted through the increasing industrialization and urbanization processes, its abolition of slavery and in the establishment of its republic. In this shift period, when the spirit of modernity produced changes in many national aspects, the male sensibilities were also affected. In the character shaping of Carlos de Melo, José Lins do Rego aimed to express the emergence of a new masculinity profile on the sugarcane elites. In order to do this investigation, we use the following sources: three novels of the author and his memories, letters, diaries, interviews, besides the other novelists' testimonies and literary criticism about the author's work. In the methodology, we use concepts of culture history and dialogue with literary theory. We analyze narrative aspects such as the structuring stories starred by Carlos de Melo, the characterization of the agrarian sugar space and the characters that made part of them, and social relationships between bosses and employees. We noticed that the author articulated a relationship between the past and the future, weaving a meaning that could explain the decadence process of the patriarchal mandate structure from the practices of being a man of Carlos de Melo. He is a person between two worlds (the rural and the urban ones) and two temporalities (the past and the present).